Highly-Educated Immigrants and Native Occupational Choice - Giovanni Peri; Chad Sparber (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2008)
Economic debate about the consequences of immigration in the US has largely focused on how influxes of foreign-born labor with little educational attainment have affected similarly-educated native-born workers. Fewer studies analyze the effect of immigration within the market for highly-educated labor. We use O*NET data on job characteristics to assess whether native-born workers with graduate degrees respond to an increased presence of highly-educated foreign-born workers by choosing new occupations with different skill content. We find that immigrants with graduate degrees specialize in occupations demanding quantitative and analytical skills, whereas their native-born counterparts specialize in occupations requiring interactive and communication skills. When the foreign-born proportion of highlyeducated employment within an occupation rises, native employees with graduate degrees choose new occupations with less analytical and more communicative content. For completeness, we also assess whether immigration causes highlyeducated natives to lose their jobs or move across state boundaries. We find no evidence that either occurs.
Keywords: F22; J61; J31; R13; 330; Immigration; Occupational Choice; Highly-Educated Workers; Communication Skills; Mathematical Skills